Limited threat of Plasmodium falciparum pfhrp2 and pfhrp3 gene deletion to the utility of HRP2-based malaria RDTs in Northern Uganda - Bosco B. Agaba; David Smith; Jye Travis; Cielo Pasay; Monica Nabatanzi; Emmanuel Arinaitwe; Isaac Ssewanyana; Susan Nabadda; Jane Cunningham; Moses R. Kamya; Qin Cheng (Malaria Journal, 2024)
Abstract Background Rapid diagnostic tests (RDTs) that detect Plasmodium falciparum histidine-rich protein-2 (PfHRP2) are exclusively deployed in Uganda, but deletion of the pfhrp2/3 target gene threatens their usefulness as malaria diagnosis and surveillance tools. Methods A cross-sectional survey was conducted at 40 sites across four regions of Uganda in Acholi, Lango, W. Nile and Karamoja from March 2021 to June 2023. Symptomatic malaria suspected patients were recruited and screened with both HRP2 and pan lactate dehydrogenase (pLDH) detecting RDTs. Dried blood spots (DBS) were collected from all patients and a random subset were used for genomic analysis to confirm parasite species and pfhrp2 and pfhrp3 gene status. Plasmodium species was determined using a conventional multiplex PCR while pfhrp2 and pfhrp3 gene deletions were determined using a real-time multiplex qPCR. Expression of the HRP2 protein antigen in a subset of samples was further assessed using a ELISA. Results Out of 2435 symptomatic patients tested for malaria, 1504 (61.8%) were positive on pLDH RDT. Overall, qPCR confirmed single pfhrp2 gene deletion in 1 out of 416 (0.2%) randomly selected samples that were confirmed of P. falciparum mono-infections. Conclusion These findings show limited threat of pfhrp2/3 gene deletions in the survey areas suggesting that HRP2 RDTs are still useful diagnostic tools for surveillance and diagnosis of P. falciparum malaria infections in symptomatic patients in this setting. Periodic genomic surveillance is warranted to monitor the frequency and trend of gene deletions and its effect on RDTs.